How liberalized is the optical fiber broadband market? Examining the role of public money in the fiber deployment in Sweden - Patrik Sandgren; Bengt G. Mölleryd (International Telecommunications Society (ITS), 2013)
This paper builds on the notion that the market for electronic communication is doing the investments in broadband. Taking its starting point in the aim for the Digital Agenda the paper examine the role of public money in the deployment of broadband networks, so called Next Generation Networks (NGA). Using a unique data set of broadband investments, the paper reveals that one of most advanced broadband nations, Sweden, is benefitting from a substantial involvement of public money. In the Swedish case, City Urban Networks, owned by municipalities and spurred by public money, have been of significant importance. Through the City Urban Networks, a real alternative to the incumbent has been established and increased roll out and uptake of fiber has taken place. The public money has altogether shrugged the market and provided more choices to the consumers - while at the same time making the broadband target set in the agenda reachable.
Keywords: 330; Next Generation Networks; fiber networks; City Urban Networks; super fast broadband; investments; Digital Agenda; broadband targets